An Introduction to Ecclesiology : Historical, Global, and Interreligious Perspectives - Kärkkäinen, Veli-Matti (InterVarsity Press, 2021)
"Major theological traditions, including Eastern Orthodox, Roman Catholic, Reformed, and Pentecostal ecclesiological insights from Latin American, Africa, and Asia distinct perspectives from women, African Americans, and recent trends in the United States key elements of the church such as mission, governance, worship, and sacraments interreligious comparison with Jewish, Islamic, Hindu, and Buddhist communities"--